Pengaruh Model Experiential Learning Terhadap Keaktifan Belajar Siswa - Rizkiana, Desti; Mahluddin; Matvayodha, Gupo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low participation in class discussions and the lack of questions asked to teachers, making students tend to be passive in the learning process. The monotonous and uninteresting learning activities make students feel bored and unmotivated to learn. In addition, the lack of opportunities for students to experience and practice the learning material directly is also an obstacle in understanding the concepts taught. Therefore, efforts are needed to increase student learning activity by giving treatment with a more interactive and experience-based learning model, namely the Experiential Learning Model. The purpose of this study is to determine whether there is a significant effect of using the experiential learning model on the learning activity of fourth-grade students at MI Darussalam Jelutung. This research is a quantitative study using a one-group pretest-posttest design, while data collection is done using a questionnaire technique and analyzed with normality test and T-test. The results showed that there was an increase in the questionnaire score before and after using the Experiential Learning Model, which can be seen from the average score before 56.70 and the average score after 61.10. Researchers found that the use of the experiential learning model has a significant effect on the learning activity of fourth-grade students at Madrasah Ibtidaiyah Darussalam Jelutung. The results of the significance level analysis are 0.003, because the value of 0.003 < 0.05, then (Ho) is rejected and (Ha) is accepted, which means the use of the experiential learning model has a significant effect on student learning activity.